Crack detection of ceramic tile using acoustic emission - Sarkawi, Buang. (Universiti Malaysia Sarawak, UNIMAS, 2005)
The crack behaviour of brittle engineering material such as ceramic tiles is deeply related to m icro cracking propagation and brittle fracture that occur in microstructure . In the present study, the Acoustic Emission method is applied to obtain certai n information required from the crack activities in the stress condition of ceramic tile . Some of the crack parameter such as acoustic emission (dB), amplitude (mV) and signal energy (ergs) can be measured by the analysis of acoustic emission signal that g ener ated. Moreover, t he number of micro crack event can be identified by the ring down counting technique. The arithmetic average calculation from 25 samples of ceramic tiles with varies of load speed have been conducted to achieve more accurate results . T hroughout the project, t he correlation between the acoustic emi ssion and crack behaviour was obtained by considering the microstructure features that existed in the ceramic tiles.